Technological Education, Importance, Principles and Functions: التكنولوجية التعليم اهمية ومبادئه ووظائفه - Alviyatul Qodri; Maskud Maskud (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2021)
Learning will be successful if all components support each other from teaching materials, methods, media, and learning evaluations. All these aspects must be considered to achieve learners' success in learning. Learning Media is needed as a tool that supports the success of learning. In the Learning media, there are parts. This method uses descriptive qualitative methods that describe the importance of technology and its parts in it. The research method used is a qualitative literature review. The results of this study are: 1) knowing the understanding of learning technology needed by everyone, especially in learning, and 2) knowing what parts exist in learning technology. سيكون التعلم ناجحًا إذا كانت جميع المكونات تدعم بعضها البعض من خلال المواد التعليمية والأساليب والوسائط وتقييم التعلم. يجب مراعاة كل هذه الجوانب بالكامل لتحقيق نجاح الطالب في التعلم. هناك حاجة إلى وسائط التعلم كأداة تدعم نجاح التعلم. توجد أجزاء في وسائط التعلم. تستخدم هذه الطريقة أسلوبًا وصفيًا نوعيًا يصف أهمية التكنولوجيا وأجزائها. طريقة البحث المستخدمة هي مراجعة الأدبيات النوعية. نتائج هذه الدراسة هي ۱) معرفة فهم التكنولوجيا التي يحتاجها الجميع ، وخاصة في التعلم ۲) معرفة الأجزاء الموجودة في التكنولوجيا.